EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN CABAI RAWIT DI KECAMATAN WAGIR, KABUPATEN MALANG - Januardi Fransiskus Simanjuntak; Christanti Agustina; Mochtar Lutfi Rayes (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Land characteristics are factors that affect crop productivity. Different conditions of land characteristics will cause differences in crop productivity. Evaluation of land suitability can be used as a basis in assessing land quality to determine the factors of land characteristics that cause differences in crop productivity. The purpose of this study was to determine actual land suitability for cayenne pepper, determine which land characteristic affect crop productivity, and modify land suitability based on actual productivity suitability classes. This study was conducted in Wagir District, Malang Regency with a survey method on 8 Land Map Units (LMU) with 42 observation points. Quantitative parameters observed in this study include soil texture, pH, CEC, C-Organic, base saturation, N-total, P-available, exchangeable K, Ca, Mg, Na, and productivity of cayenne pepper in the field. Data analysis was performed by correlation test and multiple regression with the stepwise method. The results showed the actual land suitability class of cayenne pepper in the study area was S3 and N. Modifications to the characteristics of the land that most influence the productivity of cayenne pepper in the field, namely the pH of the soil produce new criteria with classes S1: 6.0-7.6; S2: 5,7–6,0; S3: 4,6-5,7; and N: <4,6. The land suitability assessment using the modified criteria resulted in the S3 conformity class, which was similar to the percentage productivity class and the N conformity class that was similar to the percentage productivity class.